A new species of Volvariella (Agaricales, Basidiomycota) from West Bengal, India - Chattopadhyay, Pinaki; Talukdar, Mousumi; Beypih, Jeswani; Tayung, Kumananda; Dutta, Arun Kumar (Phytotaxa, 2022)
A new species, Volvariella bilobata, has been described herein from West Bengal, India. Field photographs of the basidiocarps were provided and the new species were compared with its allied taxa based on morphological and molecular (nrITS sequence) data. Volvariella bilobata was characterized by a medium sized, entirely greyish brown pileus with fibrillose surface; close to crowded lamellae coloured greyish white to greyish orange; a bilobed saccate volva with greyish brown outer surface and greyish white inner surface; smaller basidiospores measuring 4.8–5.5 × 2.7–3.5 µm; clavate to ventricose lageniform cheilocystidia measuring 32–83 × 13–30 µm; variously shaped pleurocystidia measuring 18.5–27.5 × 7–10 µm; habitat on soil; and unique sequences. Detailed morphological description with illustrations and phylogenetic tree based on molecular sequence data revealed it to be a new species.